Culture, Power, and Control: A Discussion of Autonomy and Responsibility - Alonso, Loren A (2019)
The purpose of this thesis is to explore how power, control, autonomy, and responsibility are active participants in culture and daily human life. First, I discuss two understandings of power, structured and diffused. I examine some different techniques of power that help support and reproduce the current power systems in place and how historically, these systems have been predominantly unjust. I then discuss an alternative view of power that incorporates both structured and diffused forms of power. I explain why this new understanding of power could be more useful in actively shifting the current unjust power structures present in the world today towards power structures that are more just. I build this argument using some of Michel Foucault and Noam Chomsky's explorations of power. From there, I explore how understanding power can affect how people understand and practice human autonomy and develop or agentic skills. Finally, I use a collective conception of autonomy and the disparate effects of privilege to investigate how responsibility can apply to people individually and collectively